2005
DOI: 10.1093/nar/gki704
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of 4'-thioribonucleosides and thermodynamic stability and crystal structure of RNA oligomers with incorporated 4'-thiocytosine

Abstract: A facile synthetic route for the 4′-thioribonucleoside building block 4′SN (N = U, C, A and G) with the ribose O4′ replaced by sulfur is presented. Conversion of l-lyxose to 1,5-di-O-acetyl-2,3-di-O-benzoyl-4-thio-d-ribofuranose was achieved via an efficient four-step synthesis with high yield. Conversion of the thiosugar into the four ribonucleoside phosphoramidite building blocks was accomplished with additional four steps in each case. Incorporation of 4′-thiocytidines into oligoribonucleotides improved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Selenium Derivatization at the 4'-Position. The replacement of the sugar-ring Oatom (at the 4'-position) of nucleosides and nucleic acids by the S-atom has been applied to the modification of aptamers and siRNA, as well as gene regulation [79] [80]. The synthesis of the corresponding Se counterparts has been quite challenging.…”
Section: 22mentioning
confidence: 99%
“…Selenium Derivatization at the 4'-Position. The replacement of the sugar-ring Oatom (at the 4'-position) of nucleosides and nucleic acids by the S-atom has been applied to the modification of aptamers and siRNA, as well as gene regulation [79] [80]. The synthesis of the corresponding Se counterparts has been quite challenging.…”
Section: 22mentioning
confidence: 99%
“…Although this puts limitations on the use of this modification in antisense applications, where RNase H-mediated degradation of the target mRNA is considered important for efficacy, the properties of the s 2 U, m 5 s 2 U and m 5 s 2 Umoe modifications may render them of interest for use in siRNAs. Together with DNA phosphorothioates (8) and 4′-thio-RNA (3,48,49), they constitute the third class of sulfur-modified nucleic acid building blocks with promising features for the generation of nucleic acid therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…The 4'-thio RNA exhibits very useful biophysical properties [57,58,60,63]. The 4'-thio RNA/4'-thio RNA homoduplexes (next to the LNA/LNA duplexes, see the next chapter) are among the most stable modified RNA duplexes [57].…”
Section: '-Thio Rnamentioning
confidence: 99%
“…Very recently, Haeberli et al [63] reported a very efficient synthesis of 18 starting from the pyranoside 22 (Fig. 9, Route 3) available from L-lyxose in a simple two step "one pot" procedure.…”
Section: '-Thio Rnamentioning
confidence: 99%
See 1 more Smart Citation